Can the mild clinical course of crimean–congo hemorrhagic fever in children be explained by cytokine responses?. Issue 11 (25th July 2013) - Ozsurekci, Yasemin; Arasli, Mehmet; Oncel, Eda Karadag; Caglayik, Dilek Yagci; Kaya, Ali; Icagasioglu, Fusun Dilara; Engin, Aynur; Korukluoglu, Gulay; Elaldi, Nazif; Ceyhan, Mehmet
Abstract Cytokines are possibly one of the factors responsible for death due to Crimean–Congo hemorrhagic fever (CCHF). This study aimed to determine the differences between the cytokine levels in children and adult patients with CCHF; the influence of cytokines; and the severity of the course of the disease, which seems to be milder in children. Thirty‐four children and 36 adult patients diagnosed with CCHF between 2010 and 2011 were included in this study. Diagnosis was performed by serology or by the polymerase chain reaction for CCHF virus. Levels of IFN‐γ, TNF‐α, IL‐1β, IL‐2, IL‐4, IL‐5, IL‐6, IL‐9, IL‐10, IL‐12 p70, IL‐13, IL‐17A, and IL‐22 were measured in all serum samples. Although the disease had a fatal course in three adult patients, there were no deaths in children. Statistically significant differences were not observed between the cytokine concentrations in the adults and children. No differences were detected between the serum cytokine levels in the children with moderate and those with a severe clinical course of the disease. In the adult patients with fatal outcome, significantly higher serum levels of IL‐2, IL‐5, IL‐9, IL‐12 p70, and IL‐13 were detected as compared to the cytokine levels in patients who survived the infection. No differences were detected between the serum levels of IFN‐γ, IL‐1β, IL‐17A, IL‐22, IL‐10, IL‐6, IL‐4, and TNF‐α in the patients who died and those who survived. Thus, the milder clinical course in children with CCHF cannot be explained by the cytokine network alone. The incomplete maturation of the immune system and timing and scale of immune responses could change the outcome dramatically. J Med. Virol. 85:1955–1959, 2013. © 2013 Wiley Periodicals, Inc.